IMPLEMENTASI KEBIJAKAN PENGUKURAN KINERJA PENYULUH PROGRAM KEPENDUDUKAN KELUARGA BERENCANA DAN PEMBANGUNAN KELUARGA (KKBPK) MELALUI APLIKASI E-VISUM DI PERWAKILAN BKKBN PROVINSI BANTEN - Eko Sigit Raharjo; Roy Valiant Salomo (Jurnal Reformasi Administrasi : Jurnal Ilmiah untuk Mewujudkan Masyarakat Madani, 2019)
The National Population and Family Planning Agency (BKKBN) is one of the agencies in Indonesia that has a State Civil Apparatus (ASN) with a functional position of extension. Since Law No. 23 of 2014 concerning Regional Government was published, the Management of Family Planning Extension (PKB) and Family Planning Field Officers (PLKB) was the authority of the Central Government and BKKBN mandated as an agency for the management and management of PKB. As an Agency that has carried out bureaucratic reform, BKKBN has implemented performance standards that can be measured and receive performance benefits for its employees. After the PKB and PLKB join automatically they also get the same right to receive the performance fiance. Therefore a tool is needed to be able to monitor and measure the performance of PKB and PLKB in charge in the field. BKKBN developed an online smartphone-based application called E-Visum. This study aims to determine the extent of the implementation and implementation of a recent system change to measure the performance of family planning instructors. The type of research used in this study is a type of analytical descriptive research through a qualitative approach. Data sources used in the form of primary data derived from the results of in-depth interviews with research informants and secondary data in the form of archives and documentation. The informant selection technique uses purposive sampling. The results of the study found that the implementation and application of the E-Visum application had gone well but was not optimal. In practice, the E-Visum application can still be manipulated, the monitoring system which is expected to monitor performance well has not been able to be implemented maximally because of constraints on limited staff at the central and provincial BKKBN as well as Regional Organizations (OPD) and Families Planning (KB) at the Regency / City level which is still under the Regional Government. PKB conditions which on average are already old at night also cause difficulties in the operation of smartphones.